Diseño de la superestructura del puente peatonal de hormigón armado frente al paseo shopping de la Ciudad de Machala - Tinoco Balbuca, Gabriel Fernando (My University, 2020)
The following report is aimed at the DESIGN OF THE SUPERSTRUCTURE OF THE PEDESTRIAN BRIDGE OF REINFORCED CONCRETE IN FRONT OF THE PASEO SHOPPING OF THE CITY OF MACHALA in the aforementioned place there is a large pedestrian influx that come from the different cantons of the province, where for safety of For people, a pedestrian bridge design has been found convenient to guarantee the crossing of people to the Paseo Shopping Mall. Applying the technical specifications of the design and construction of reinforced concrete structures, the superstructure will be designed in accordance with the current regulations specified in the Ecuadorian construction standard NEC-2015, Regulation Requirements for Structural Concrete ACI318S-14 and the Ecuadorian Technical Regulation RTE INEN 004-2.2011. Specifically, the structural elements such as the handrails, the posts that will support the railings, the curb, slab and beam will be designed, with the aforementioned specifications, we will proceed step by step with each structural element, in this way the development of the corresponding calculations is argued.
El siguiente informe está dirigido al DISEÑO DE LA SUPERESTRUCTURA DEL PUENTE PEATONAL DE HORMIGON ARMADO FRENTE AL PASEO SHOPPING DE LA CIUDAD DE MACHALA en el lugar antes mencionado existe una gran afluencia peatonal que provienen de los diferentes cantones de la provincia, en donde por seguridad de las personas se ha visto conveniente un diseño de puente peatonal que garantice el cruce de las personas al centro Comercial Paseo Shopping. Aplicando las especificaciones técnicas del diseño y construcción de estructuras de hormigón armado, se diseñará la superestructura de acuerdo a la normativa vigente especificada en la norma ecuatoriana de construcción NEC-2015, Requisitos de Reglamento para Concreto Estructural ACI318S-14 y el Reglamento Técnico Ecuatoriano RTE INEN 004-2.2011. Específicamente se diseñara los elementos estructurales como los pasamanos, los postes que soportarán las barandas, el bordillo, losa y viga, con las especificaciones antes mencionadas se procederá paso a paso con cada elemento estructural, de esta manera se argumenta el desarrollo de los cálculos correspondientes.
Keywords: HORMIGÓN ARMADO; SUPERESTRUCTURA; CARGA VIVA; CARGA MUERTA